Properties of chicken head gelatins as affected by extraction method - Ee, S. C.; Saari, N.; Abas, F.; Ismail, A.; Abu Bakar, M. K.; Bakar, Jamilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Malaysia is a surplus poultry producing country with well-established commercial slaughtering and processing plants. Immense quantity of heads, feet, viscera, blood and feathers are usually discarded and not optimally utilized. Chicken heads are rich in protein, and could be a potential source of gelatin. The aim of the present work was therefore to find a simpler, faster, cheaper and greener gelatin extraction technology as compared to current available methods of gelatin extraction from poultry heads. A comparison of three different gelatin extraction methods with alkaline-acid pretreatment (E1), single acid pretreatment (E2) and single alkaline pretreatment (E3) were studied to extract gelatin from chicken heads. E1 and E2 produced gelatins of Type A, while E3 produced gelatin of Type B. High bloom gelatin (>300 g) with <1% of ash content, high gelling (25.8-26.0°C) and melting (30.8-32.3°C) temperatures, good functionality and physical appearance were obtained from E1 and E2 extraction methods. Gelatins of E1 and E2 had higher viscous (G’’) and elastic modulus (G’) values on cooling and heating as compared to the commercial bovine skin gelatin. FTIR spectra of the gelatins indicated different degrees of structural denaturation. Overall, extraction methods of E1 and E2 produced better gelatin quality than E3. Nonetheless, E1 was the best extraction method for the production of high quality gelatin from chicken heads.